Acute Effects of Two Doses of a Coffeeberry Extract on Mental Energy-Related Feelings and Cycling Performance After Cognitive and Physical Work. (7th June 2021) - McGranahan, Melissa; Nuccio, Ryan; Mitchell, Ellen; Pahnke, Matthew; O'Connor, Patrick
Abstract: Objectives: To assess the acute effects of two doses of coffeeberry extract use on (i) mental energy-related feelings (primary outcome) and (ii) cycling performance (secondary outcome). Methods: Twenty-eight active adults (14 females & 14 males: mean age = 20.6 ± 1.0 & 21.8 ± 3.8 years; VO2 peak = 38.6 ± 5.2 & 44.7 ± 6.9 ml.kg.min −1 ) completed a randomized, double-blind, placebo-controlled, cross-over study. Treatments were a base beverage supplemented with a coffeeberry® extract (VDF FutureCeuticals, Inc.) at doses of 100 mg (CB100) and 300 mg (CB300). The base beverage alone was the placebo (PL) and the positive control was the base beverage with 75 mg caffeine (CAF). Participants consumed one of the four beverages during visits separated by at least five days. Before (BL) and one hour post-treatment, a battery of five cognitive tests and visual analog scales assessing the mood states of alertness, energy and fatigue were completed, taking 55-minutes. Two hours post-treatment, a 20-minute high intensity interval cycling protocol was performed followed by a 3-minute time trial; heart rate, ratings of perceived exertion, and feelings of fatigue were measured. Bonferroni corrected t-tests tested differences in cycling performance ( P  < .001). Repeated measures ANOVAs tested for other treatment effects. Mean differences from BL are presented below. Results: There was a significant Beverage x Time interaction for alertness ( P  = .008), energy ( P  = .009), and fatigue ( P  = .008). Post-hoc analysis indicated from BL to POST CAF significantly improved alertness (PL: –2.2 ± 15.3; CB100: –.3 ± 11.2; CB300: 1.0 ± 11.7; CAF: 9.1 ± 12.5); energy (PL: –9.4 ± 54.7; CB100: –5.6 ± 36.4; CB300: 1.9 ± 35.9; CAF: 26.2 ± 40.8), and fatigue (PL: 11.8 ± 52.6; CB100: 6.5 ± 41.0; CB300: –.9 ± 43.9; CAF: –26.8 ± 42.9). Conclusions: Consumption of a beverage with 100 mg or 300 mg coffeeberry extract one hour before a cognitive test or two hours before a high intensity exercise bout does not influence feelings of alertness, energy, and fatigue or cycling performance. Consumption of a beverage with 75 mg caffeine had no impact on cycling performance but improved feelings of alertness, energy, and fatigue. Funding Sources: PepsiCo R&D. The views expressed in this abstract are those of the authors and do not necessarily reflect the position or policy of PepsiCo, Inc.